2020
DOI: 10.1016/j.ajic.2019.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Profiles of the bacterial community in short-term indwelling urinary catheters by duration of catheterization and subsequent urinary tract infection

Abstract: Objective: Urinary catheterization, even of short duration, increases risk of subsequent urinary tract infection (UTI). Whether the bacteria found on the surface of catheters placed for <3 days are associated with UTI risk is unknown. Methods:We screened the biofilms found on the extraluminal surface of 127 catheters placed for <3 days from women undergoing elective gynecologic surgery, using targeted qPCR and an untargeted 16SrRNA taxonomic screen.Results: Using qPCR, Enterococcus spp. were found on virtually… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 40 publications
3
2
0
Order By: Relevance
“…Enterococci’s ability to modulate the bladder environment to benefit itself and other pathogens may further explain why enterococci are described as a pioneer species on urinary catheter 23 . This supports several clinical studies that showed enterococci are early colonizers and persist during prolonged catheterization in monomicrobial or polymicrobial interactions 5 , 23 , 76 .…”
Section: Discussionsupporting
confidence: 90%
“…Enterococci’s ability to modulate the bladder environment to benefit itself and other pathogens may further explain why enterococci are described as a pioneer species on urinary catheter 23 . This supports several clinical studies that showed enterococci are early colonizers and persist during prolonged catheterization in monomicrobial or polymicrobial interactions 5 , 23 , 76 .…”
Section: Discussionsupporting
confidence: 90%
“…Enterococci’s ability to modulate the bladder environment to benefit itself and other pathogens may further explain why enterococci are described as a pioneer species on urinary catheter. This supports several clinical studies that showed enterococci are early colonizers and persist during prolonged catheterization in monomicrobial or polymicrobial interactions 5 , 23 , 67 .…”
Section: Discussionsupporting
confidence: 90%
“…Urinary catheterization is a common procedure to drain urine from patients' bladders due to chronic conditions or while in healthcare facilities, intensive care units, during surgical procedures and recovery [1][2][3] . Despite its benefits, catheter placement increases the risk of developing a catheter-associated urinary tract infection (CAUTI) [4][5][6][7] . CAUTIs are one of the most common nosocomial infections and often lead to septicemia with a 30% mortality 3,8 .…”
Section: Introductionmentioning
confidence: 99%
“…Like in a study in Nepal, Escherichia coli was the most common organism but in contrast Klebsiella pneumonae was the second in that study [ 32 ]. The gram-positive Staphylococcus aureus 68(20.7%) was the most common followed by Enterococcus 58(18%); these findings were similar to study among women in elective gynaecologic surgery where Escherichia coli was the most common gram-negative, Enterococcus and Staphylococcus were the most common gram-positive for catheters placed < 3 days [ 33 ]. A comparative study done in Egypt reported findings in line with this study where there was a difference in the prevalence of uropathogens among patients with an indwelling urinary catheter and non-catheterized patients Enterococcus (11.7%) and Pseudomonas spps (6.7%) being more common in CAUTI [ 34 ].…”
Section: Discussion Study Limitation Recommendation Conclusionsupporting
confidence: 76%